2015
DOI: 10.1177/0022487115592462
|View full text |Cite
|
Sign up to set email alerts
|

Problems Without Ceilings

Abstract: Support for new forms of teaching expertise with rigorous and equitable outcomes for student learning is a particular challenge when communities of actors working together do not share a similar language or vision of teaching practice. For this project, we coordinated activities in and outside of secondary science classrooms for cooperating teachers (CTs) and their preservice teachers (PSTs) to inquire into a set of research-based teaching practices and tools. Using frame analysis, we contrast three problems-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The results in Table 2 indicate that teachers' learning is the most appealing ranking as teachers' attitudes toward teacher education competencies developed in the Journal of Teacher Education. Seventeen papers mentioned teachers' learning regarding improving the competencies of teacher education from 2015 through 2020 (e.g., Thompson, Hagenah, Lohwasser, & Laxton, 2015;Riley & Solic, 2017;Bacon, 2020). Interestingly, our analysis also found teachers' perspectives in the second-ranking position focused on teacher education.…”
Section: From 2015 To 2020 the Trends In Teachers' Competencies In Jtesupporting
confidence: 52%
See 1 more Smart Citation
“…The results in Table 2 indicate that teachers' learning is the most appealing ranking as teachers' attitudes toward teacher education competencies developed in the Journal of Teacher Education. Seventeen papers mentioned teachers' learning regarding improving the competencies of teacher education from 2015 through 2020 (e.g., Thompson, Hagenah, Lohwasser, & Laxton, 2015;Riley & Solic, 2017;Bacon, 2020). Interestingly, our analysis also found teachers' perspectives in the second-ranking position focused on teacher education.…”
Section: From 2015 To 2020 the Trends In Teachers' Competencies In Jtesupporting
confidence: 52%
“…Several studies are focusing on competencies of teachers to improve the transformation of classroom practice, the learning of collaborative teachers, enhanced student attainment, knowledge of pedagogical content, knowledge of the subject, and experiential training by several researchers from 2015 to 2020 (e.g., Bruce & Chiu, 2015;Heineke & Giatsou, 2020). Other studies in the competencies of teacher education also reported that teachers' skills involved interpersonal and communication skills and competencies and results in instructional design (e.g., Leeferink et al, 2015;Coogle et al, 2020;Koehle et al, 2019) and teachers' attitudes can be developed by teacher individuality and professionalism (e.g., Thompson et al, 2015;López, 2017).…”
Section: From 2015 To 2020 the Trends In Teachers' Competencies In Jtementioning
confidence: 99%
“…In particular, faculty observed candidates develop LSE by applying scholarly inquiry through authentic problems of practice as noted in leadership actions and reflective dialogue. Similar to what Thompson et al (2015) discuss, the faculty serve as mentors while candidates practice inquiry in their coursework. In the change leadership course, candidates examine cases of leadership addressing problems of practice with instructor guidance.…”
Section: Theme Two: Increased Confidence As Lse In Thought and Means Impacts Self-motivation And Action To Leadmentioning
confidence: 94%
“…Participants described this impact in ways that illustrated how the program aided in strengthening their selfperceptions as leaders because they were afforded opportunities to develop critical thinking strategies and resources in which to draw on as leaders in the field. It is clear that graduates of a CPED program, with a focus on cultivating problem-solving scholar-practitioners, do benefit from an increase in overall LSE by tapping into the sub-constructs through field-based coursework on authentic problems of practice (Cunningham et al, 2019;Lenihan et al, 2015) by committed faculty mentors (Thompson et. al, 2015).…”
Section: Evaluation Summary By Research Questionmentioning
confidence: 99%
“…In an effort to support these emerging partnerships, Goodlad and his colleagues invited universities and their school districts to apply for membership in the National Network for Educational Renewal (NNER; Sirotnik, 2001). These early partnerships, supported and expanded through the NNER in three 5-year phases of implementation between 1986 and 2001 (Sirotnik, 2001), reflect the commitment of Goodlad and others to bridge the persistent research-to-practice divide, a sustained effort that has continued in general, but also in large part due to Goodlad's early efforts (see also Heineke, Ryan, & Tocci, 2015;Thompson, Hagenah, Lohwasser, & Laxton, 2015;Zeichner, Payne, & Brayko, 2015).…”
Section: Conceptual Frameworkmentioning
confidence: 99%